Between Progress and Backwardness. A Look at the Housing Policy of the Period of the People’s Republic of Poland from the Social and Economic Perspective After 1989 - Kujawa, Jakub (Studia Historiae Oeconomicae, 2020)
The article deals with the issue of the place, role and significance of the achievements of the housing policy of the Polish People’s Republic (PRL) and in the economy before and after 1989, observed from the contemporary social and economic point of view. In the period of systemic transformation, expert and opinion-makers were, in majority, critical of the achievements of the housing policy of the prior period. This led to the creation and subsequent consolidation in public discourse of the negative image of the housing construction of the PRL period. 30 years after the collapse of communism, during which time the free market economy developed and Poland became a member of EU, this topic requires a more objective look and a more focused approach to the range of socio-demographic and economic changes that took place during that period. The current perception of the problem is also influenced by the lack of solutions to the housing issue by successive governments of the Third Republic of Poland.